Smoking effect on bacteriological quality of Atlantique Mackerel (Scomber scombrus) and Horse Mackerel (Trachurus trachurus) in South Benin. - Assogba, Martinien Hospice Mahussi; SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; HOUEMENOU, GUALBERT; Silemehou, Joselyne A. S.; Gossa, Raoul; DAHOUDA, MOHAMADOU; CHIKOU, ANTOINE; FAROUGOU, SOUAÏBOU; Kpodékon, Marc; YOUSSAO ABDOU KARIM, ALASSANE (My University, 2018)
Fish is one of the most important sources of protein in South Benin. The fainting of hygiene in the processing and preservation process constitutes a potential danger to the consumer by the appearance of pathogenic germs. This study aimed to control the sanitary quality of smoked fish in the Littoral Department (Benin). Thus, data were collected on the flesh quality of Scomber scombrus and Trachurus trachurus from June to December 2015 at Wlacodji in South Benin. No difference was observed between bacterial loads of Scomber scombrus and Trachurus trachurus. The TMAF load was higher (P<0.05) in fresh fish (39.56 x 10 3 CFU/g) than in smoked fish (0.752 x 10 3 CFU/g). Total colifo rm load was higher in fresh fish than in smoked fish (0.705 x 10 3 3 vs 0.0025 x 10 CFU/g, P<0.001). Similarly, fecal coliform load was higher in fresh fish (0.365 x 10 3 CFU/g) than in s moked fish 3 (0.0026 x 10 CFU/g, P<0.05). Staphylococcal contamination rate was 0.17% and 0.06%, respectively, in fresh and smoked fish. Contrary to fresh fish, no cases of salmonella and SRA were counted in smo ked Horse mackerel and Atlantic mackerel. The smoking performed in good hygienic conditions reduces the bacteriological load of fish.
Keywords: smoking; microbiology; bacteria; hygiene; Benin.